Water for Firefighting in Sol Plaatje Municipality, Northern Cape, South Africa - Thage, Tumelo MacAurthur (University of the Witwatersrand, Johannesburg, 2023)
In South Africa, SANS 10090 (SABS, 2018a) and the Red Book (DHS & CSIR, 2019) recommend that for firefighting municipal water distribution systems must have and maintain the capacity to provide water for firefighting purposes. van Zyl & Haarhoff (2007) state that the provision of water for firefighting is a dominant design consideration as it influences the sizing and outputs of critical components. Scheepers (2012) argues that fire flows acts ‘as the most limiting demand condition’ as when it required it is extracted in large quantities for a short period. The most commonly used fire flow values in the SANS 10090 have largely remained unchanged for several decades. In other words, these values have not been revised to take account of the evolution of municipal water consumption over more than 30 years. This suggests that the recommended water requirements for firefighting may no longer be fit for purpose. The literature review revealed that the fire flows in the Red book violates the same in the SANS 10090 - this is illegal as the SANS 10090 specifies enforceable absolute limits. Furthermore, the Red book and SANS 10090 provide different fire risk classifications and values for the different parameters and as such, inconsistent and lack uniformity. It is important for design engineers to have accurate input data when planning and designing for fire flow requirements as any deficiency in basic design information could lead to an insufficient capacity to fight fires or an over-design of water supply infrastructure. A question arose from these observations, which provided inspiration for this study: Are fire flows in the SANS 10090 and Red book appropriate for current firefighting efforts? In answering this question, the first step of this study was to identify participating municipalities that were willing to release their datasets on firefighting for this study. Sol Plaatje municipality was one of the willing municipalities. This study thereafter categorised and analysed information contained in the 3236 fire incident reports that occurred within Sol Plaatje Municipality during the period 21 July 2017 to 21 August 2020, and compared actual fire flow volumes and flow rate data against the SANS 10090, Red book and previous South African studies. In order to provide context and aid better understanding of the datasets, structured interviews were conducted with municipal officials responsible for firefighting operations at Sol Plaatje municipality. Key highlights of this study indicated: ∼ 93.3% of fires in Sol Plaatje municipality were extinguished using 7 Kℓ or less of water. This result is similar to previous studies- In a 2014 study more than 90% of fires in 5 Western Cape Towns were extinguished using less than 10 Kℓ of water; In a 2019 study, 75% of fires in the City of Johannesburg were extinguished using less than 6.60 Kℓ of water; and In a 2022 study, 87% of fires in the City of Johannesburg were extinguished using 10 Kℓ or less of water. Overall, 75%-93% of fires were extinguished in the various study areas using 10 Kℓ or less of water. For large fires in Sol Plaatje municipality, the average water volume used to extinguish 85 large Category 2 fires was 8.56 Kℓ or less of water. This finding is similar to that of the Western Cape 2014 study and the 2022 City of Johannesburg study that found that 8.6 Kℓ and 9.63 Kℓ or less of water extinguished 77 and 89 large category 2 fires, respectively. What is evident from the results is that the volumes of water used in Sol Plaatje and previous studies are significantly less that the specified values in SANS 10090 and the Red book. An adverse consequence of higher values is that it leads to an over-design of water supply infrastructure as it increases the volume of municipal storage required for firefighting and consequently, increases the total capacity of municipal storage. Increased storage capacity increases resources that are expended, as well as water retention times, which negatively affects water quality. This study validates the recommendations of previous studies that the fire flows in the SANS 10090 and Red book need to be revised to enable the efficient conservation of scarce water resources and optimal design of water systems.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Science in Engineering, in the School of Civil and Environmental Engineering, in 2024.
Keywords: Water for firefighting; SANS 10090; Red book; South Africa; Firefighting municipal water distribution systems; Sol Plaatje municipality; UCTD; SDG-6: Clean water and sanitation